A conceptual framework for understanding the environmental impacts of ultra-processed foods and implications for sustainable food systems. (25th September 2022) - Anastasiou, K.; Baker, P.; Hadjikakou, M.; Hendrie, G.A.; Lawrence, M.
Abstract: Minimising environmental impacts and prioritising the production of nutritious foods are essential qualities of a sustainable food system. Ultra-processed foods (UFPs) are potentially counterproductive to these objectives. This review aims to summarise the magnitude and types of environmental impacts resulting from each stage of the UPF supply chain and to develop a conceptual framework to display these impacts. It also aims to identify the terms used to describe UPFs in the sustainability literature, and the methods used to measure the associated environmental impacts. A narrative review approach with a systematic search strategy was used. Fifty-two studies were included that either described or quantified the environmental impacts of UPFs. This review found that UPFs are responsible for significant diet-related environmental impacts. Included studies reported that UPFs accounted for between 17 and 39% of total diet-related energy use, 36–45% of total diet-related biodiversity loss, up to one-third of total diet-related greenhouse gas emissions, land use and food waste and up to one-quarter of total diet-related water-use among adults in a range of high-income countries. These results varied depending on the scope of the term used to describe UPFs, stages of the lifecycle included in the analyses and country. Studies also identified that UPF production and consumption has impacts on land degradation, herbicide use, eutrophication and packaging use, although these impacts were not quantified in relation to dietary contribution. The findings highlight that environmental degradation associated with UPFs is of significant concern due to the substantial resources used in the production and processing of such products, and also because UPFs are superfluous to basic human needs. The conceptual framework and findings presented can be used to inform food policy and dietary guideline development, as well as provide recommendations for future research. Highlights: Ultra-processed food production uses significant finite environmental resources. Ultra-processed foods are responsible for significant environmental degradation. Environmental impacts are driven by intense production methods & overconsumption. Environmental impacts are avoidable; ultra-processed foods are not nutritionally essential. The framework developed can inform food policies and future research.